2010
DOI: 10.1007/s10800-010-0202-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption properties and inhibition of mild steel corrosion in hydrochloric acid solution by ceftobiprole

Abstract: The inhibition effect of ceftobiprole against the corrosion of mild steel in 1 M HCl solution was studied by weight loss, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and atomic force microscopy techniques. Inhibition efficiency increased with inhibitor concentration where as decreased with acid concentration. Data obtained from EIS studies were analyzed to model the corrosion inhibition process through appropriate equivalent circuit models. The adsorption of ceftobiprole obeyed L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 59 publications
1
34
1
Order By: Relevance
“…It can be considered as one of the worst technical calamity. The study of corrosion inhibition of mild steel has received considerable amount of interest because of the wide usage of mild steel as constructional material in many industries [1][2][3]. The wide spread applications of mild steel in various industries is mainly due to its excellent mechanical properties and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…It can be considered as one of the worst technical calamity. The study of corrosion inhibition of mild steel has received considerable amount of interest because of the wide usage of mild steel as constructional material in many industries [1][2][3]. The wide spread applications of mild steel in various industries is mainly due to its excellent mechanical properties and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…One might also expect that the mechanism is prevented in other way according to the equations (11-13). If protonation of the cupral molecules occurs then the availability of excess negative charge on the surface electrode (Singh and Quraishi, 2011) will become associated with the protective layer as (MCl cupral ) . or (MSO cupral ) .…”
Section: Inhibition Mechanism Of Corrosionmentioning
confidence: 99%
“…This decrease in C dl results from a decrease in local dielectric constant and / or an increase in the thickness of the double layer, suggested that inhibitor molecules inhibit the mild steel corrosion by adsorption at the metal / acid interface [23]. The depression in Nyquist semicircles is a feature for mild steel electrodes and often referred to as frequency dispersion and attributed to the roughness and other inhomogeneties of the mild steel [24].…”
Section: Electrochemical Impedance Studiesmentioning
confidence: 99%